2019
DOI: 10.1111/1462-2920.14706
|View full text |Cite
|
Sign up to set email alerts
|

Cwp22, a novel peptidoglycan cross‐linking enzyme, plays pleiotropic roles in Clostridioides difficile

Abstract: Summary Clostridioides difficile is a Gram‐positive, spore‐forming, toxin‐producing anaerobe pathogen, and can induce nosocomial antibiotic‐associated intestinal disease. While production of toxin A (TcdA) and toxin B (TcdB) contribute to the main pathogenesis of C. difficile, adhesion and colonization of C. difficile in the host gut are prerequisites for disease onset. Previous cell wall proteins (CWPs) were identified that were implicated in C. difficile adhesion and colonization. In this study, we predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 81 publications
1
33
0
Order By: Relevance
“…The severity of infection was clearly indicated in the mice infected with the R20291 lrp mutant strain, attributed to smaller cecum size and less well-formed feces, as well as more extensive necrosis and inflammation, as revealed by histological examination. It has been suggested in the past that clindamycin administration prior to challenge with C. difficile select for Clostron-based mutants bearing the ermB cassette, although other studies in which Clostron-based mutants with reduced virulence in vivo have also been reported (Ünal et al, 2018; Zhu et al, 2019). However, for further clarification, we are in the process of obtaining a markerless lrp mutant using the recently developed RiboCas system (Cañadas et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The severity of infection was clearly indicated in the mice infected with the R20291 lrp mutant strain, attributed to smaller cecum size and less well-formed feces, as well as more extensive necrosis and inflammation, as revealed by histological examination. It has been suggested in the past that clindamycin administration prior to challenge with C. difficile select for Clostron-based mutants bearing the ermB cassette, although other studies in which Clostron-based mutants with reduced virulence in vivo have also been reported (Ünal et al, 2018; Zhu et al, 2019). However, for further clarification, we are in the process of obtaining a markerless lrp mutant using the recently developed RiboCas system (Cañadas et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…When we started looking for new anti-CD vaccine antigens, the Cwp22 protein was identified bioinformatically as one of the cell wall proteins [35]. Next, it was found in the CD proteome [36], characterized [29] and recently, predicted to be a good vaccine antigen by Zhou et al [13]. Now, we are the first to identify Cwp22 protein as an immunoreactive one using CDI patient sera.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained using different extraction method. Wright, et al used TS buffer (10 mM Tris/HCl (pH 6.9), 10 mM MgCl2, 0.5 M sucrose) with the addition of mutanolysin, lysozyme, lysostaphin, RNase and 4-(2-aminoethyl)benzenesulfonyl fluoride hydrochloride which mostly extracted proteins of pI between 4 and 6, whereas Cwp22 protein pI is 8.89 [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 In fact, recently, Cwp22 has also been shown to be involved in toxin production, sporulation, motility, and cell viability in C. difficile strain R20291. 37 CwpV promotes C. difficile aggregation and its strain-dependent structural variations may assist in evading the host antibody response 38 or to launch an antiphage strategy. 39 Disseminating spores, on the contrary, make use of the hydrophobic exosporium to adhere to and colonize surfaces.…”
Section: Discussionmentioning
confidence: 99%